KUALITAS LAYANAN PAJAK DAN PAJAK DIGITAL TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI UMKM - Kamil, Islamiah; Yolifiandri, Yolifiandri; Prihanto, Hendi; Estiarto, Lintang Putri; Azkiah, Neza (Unversitas Prof. Dr. Moestopo (Beragama), 2025)
The urgency of this study stems from the growing significance of tax digitalization in Indonesia, particularly for Micro, Small, and Medium Enterprises (MSMEs). The quality of tax services, including the application of Digital Service Tax (DST), plays a crucial role in enhancing taxpayer compliance. Digitalizing the taxation system fosters greater transparency and efficiency in tax administration. However, challenges remain, particularly regarding taxpayers' understanding of digital services. Consequently, it is essential to examine the impact of tax service quality and digital tax implementation on individual taxpayer compliance within MSMEs in the context of digitalization. The objective of this research is to evaluate how tax service quality and the application of DST influence the compliance levels of individual MSME taxpayers. Employing a quantitative approach, the study collects data through surveys distributed to MSME taxpayers across the Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) areas. The data will be analyzed using multiple linear regression to determine the relationship between tax service quality, digital tax, and tax compliance variables. The anticipated outcomes of this research include the publication of findings in accredited scientific journals and the formulation of policy recommendations for the Directorate General of Taxes to enhance digital tax service quality, thereby improving compliance among MSME taxpayers.